Recognition of the critically ill patient and escalation of therapy. Issue 11 (November 2021) - Brown, Amy; Ballal, Apoorva; Al-Haddad, Mo
Abstract: Critical illness often involves multiple organ failures and is associated with significant morbidity and mortality. In the vast majority of patients, there is a recognizable period of physiological deterioration which heralds the development of organ failure and critical illness. Despite efforts to improve the detection and management of critical illness, signs of deterioration are often missed and decisions to move patients to critical care units are delayed. Standardized approaches which implement an effective 'chain of response' are now utilized worldwide. They focus on attempting to reduce the incidence of serious adverse events (SAEs) such as in-hospital cardiac arrest and unplanned intensive care unit (ICU) admission using preventative measures. These systems should include: accurate recording and documentation of vital signs, recognition and interpretation of abnormal values, rapid bedside patient assessment by trained teams and appropriate interventions. Early warning systems (EWS) are an important part of this and can help identify patients at risk of deterioration and SAEs. Assessment of the critically ill patient should be undertaken by an appropriately trained clinician and follow a structured ABCDE (airway, breathing, circulation, disability and exposure) format. This facilitates correction of life-threatening problems by priority and provides a standardized communication framework between professionals. Lastly, timely support and input from members of the critical care team are vital to ensure optimal outcomes for critically ill patients.